On Stability for Hybrid System under Stochastic Perturbations - Tan Binh, Cao; Cong Son, Ta (VNU Journal of Science: Mathematics - Physics; Vol 37 No 1DO - 10.25073/2588-1124/vnumap.4522, 2021)
The aim of this paper is to find out suitable conditions for almost surely exponential stability of communication protocols, considered for nonlinear hybrid system under stochastic perturbations. By using the Lyapunov-type function, we proved that the almost surely exponential stability remain be guaranteed as long as a bound on the maximum allowable transfer interval (MATI) is satisfied.